Effect of the Hypoxia Inducible Factor on Sorafenib Resistance of Hepatocellular Carcinoma - Zeng, Zhi; Lu, Qiliang; Liu, Yang; Zhao, Junjun; Zhang, Qian; Hu, Linjun; Shi, Zhan; Tu, Yifeng; Xiao, Zunqiang; Xu, Qiuran; Huang, Dongsheng (Frontiers in Oncology, 2021)
Sorafenib a multi-target tyrosine kinase inhibitor, is the first-line drug for treating advanced hepatocellular carcinoma (HCC). Mechanistically, it suppresses tumor angiogenesis, cell proliferation and promotes apoptosis. Although sorafenib effectively prolongs median survival rates of patients with advanced HCC, its efficacy is limited by drug resistance in some patients. In HCC, this resistance is attributed to multiple complex mechanisms. Previous clinical data has shown that HIFs expression is a predictor of poor prognosis, with further evidence demonstrating that a combination of sorafenib and HIFs-targeted therapy or HIFs inhibitors can overcome HCC sorafenib resistance. Here, we describe the molecular mechanism underlying sorafenib resistance in HCC patients, and highlight the impact of hypoxia microenvironment on sorafenib resistance.